Guselkumab, tildrakizumab, and risankizumab in a real-world setting: drug survival and effectiveness in the treatment of psoriasis and psoriatic arthritis - Cathrine Dawn Büttner Elgaard; Lars Iversen; Kasper Fjellhaugen Hjuler (Taylor & Francis Group, 2023)
Background Clinical trials have shown promising results for interleukin-23 inhibitors in the treatment of psoriasis. The drugs have been used in clinical practice since 2017. Objective To investigate the drug survival and effectiveness of interleukin-23 inhibitors in the treatment of psoriasis and psoriatic arthritis (PsA) in a real-world setting. Methods The study was a retrospective analysis of patients treated with either guselkumab, tildrakizumab, or risankizumab at the Department of Dermatology, Aarhus University Hospital, during the period from June 11 2018, to July 14 2021. Results A total of 80 patients were included. During the study, 19 patients discontinued treatment with an interleukin-23 inhibitor, and mean treatment duration (SD) was 61.4 weeks (43.7). Seventy-six patients (95%) had previous use of ≥1 biologic. One-year drug survival was 81.0%. Among patients, 64.3% achieved a Psoriasis Area and Severity Index (PASI) ≤ 2 at weeks 12-17; 61.3%, at weeks 40-60. There was no statistically significant difference between the drugs regarding the chance of achieving PASI ≤ 2 (p>.05). Twenty-two patients (27.5%) had PsA. Among these, 40.9% and 36.4% achieved complete remission and partial remission, respectively. Conclusions Interleukin-23 inhibitors appear to have high and similar drug survival and effectiveness in patients with difficult-to-treat psoriasis and PsA.